Lyme disease in Rottweiler dog: Case report - Pereira, Ana Beatriz Américo; Sodré Moreno, Brenda Fernanda; Galeno, Lygia; Mendes Alves, Andressa; Conceição Fonseca, Walkyria; Reis de Carvalho, Sávio Matheus; Gonçalves Moraes, Karoline; Bastos Rodrigues, Ana Clara; Azevedo Carvalho, Victor Hugo (Pubvet, 2018)
Lyme disease is a zoonosis that is rarely reported in Brazil and the dog behaves as a reservoir in the home environment, which favors the transmission of the pathogen to humans and other animals. Thus, the objective of this study was to report the presence of anti-Borrelia burgdorferi antibodies in a dog attended at a clinic in São Luís - MA. Lyme disease or Lyme borreliosis is an infectious disease of worldwide distribution, determined by spirochetes of the genus Borrelia, which affects different species of domestic animals, wild and also man. It was attended in a private clinic, a dog of the breed Rottweiler, male, 01 year old with the complaint of apathy, bilateral ocular secretion and presence of ectoparasites. Physical examination showed that the animal was thin, conjunctival and oral mucosae hypocorate, submandibular, pre-scapular and popliteal lymph nodes normal to palpation and without alterations to pulmonary and cardiac auscultation. The present case allowed to conclude that the clinical and hematological alterations may be non-specific, however in regions where the incidence of ticks is of great relevance and because it is a zoonosis, it becomes important to investigate borreliosis in animals with a history of ticks. The precise diagnosis of canine borreliosis should be made in order to institute the appropriate therapy for the case. Control of vectors is of paramount importance, since they are responsible for the transmission of borreliosis. Therefore, it is necessary that the Veterinarian’s guidance is given to the owners of infected animals, minimizing the risks to human and animal health.